Efficacy of Commercial Symbiotic Bio-Fertilizer Consortium for Mitigating the Olive Quick Decline Syndrome (OQDS) - Giovannetti Giusto; Polo Flavio; Nutricato Sara; Masoero Giorgio; Nuti Marco (Journal of Agronomy Research, 2019)
The inoculation of soil with a bio-fertilizer (BF), with arbuscular mycorrhiza fungi, characterizes a Symbiotic (S) agriculture mode, aimed at promoting the yield and health of crops through modifications in the rhizosphere as well as in the plant phenotype. The main objective of this study was to reduce the incidence of Olive Quick Decline Syndrome (OQDS, involving Xylella fastidiosasubsp.pauca) that afflicts the olive groves in Apulia (Italy). Non-inoculated control (C) plants were compared with Symbiotic (S) plants inoculated with 20 kg ha-1 of Micosat F ®, through a 15 cm deep scarification, in the groves of seven farms covering an area of 27 ha. In addition to a visual observation of 484 plants, to obtain a gradation of the disease severity, some objective rapid type methods were utilized to survey the plants and soil , namely leaf pH, NIR tomoscopy of the leaves, hay-litter-bag probes coupled with NIR spectroscopy and the prediction of soil induced respiration. The fingerprinting of the S and C types of leaves and litter-bags was ascertained by means of the use of a random forest algorithm in the classification matrices. The results on the symptoms appeared variable: they were significantly mitigated in two groves out of six, but they were aggravated in one. All the rapid measurements became essentials in a “holistic” model which was able to explain over 95% of the average mitigation / null / aggravation response to BF inoculation. The holistic model gathers differential and compositional analyses of the leaf (pH, crude protein, water) and of the soil (respiration), but depends mainly on the fingerprinting of the C and S leaves and litter-bags. Two keys were identified for a successful inoculation: a high degree of variability of the soil conditions permitting hospitality for the BF with enhancement of the microbial activity in the S soil (lowering the fingerprint of the control litter-bags) and homogeneity of the leaves (with increases in the fingerprint of the S leaves treated with BF). In short, the inoculation of diseased plants with one BF consortium is far from being the ultimate remedy to mitigate OQDS in all situations. Further studies are needed, at a field level, to clarify the soil hosting capacity and to define the mycorrhizal and / or endophytic * plant * pathogen interactions, even using rapid methods.
Keywords: Olive